(untitled) (Journal of Guidance and Counselling Studies, 2021)
This study investigated students’ test anxiety as a predictor of their attitude towards examination malpractice in Anambra sate.Three research questions were answered and one hypotheses were tested at 0.05 levels of significance. Correlation research design was adopted for this study. The population for this study consisted of 23,396 Senior Secondary School (SS2) students. The sample consisted of 1458(606male and 852female) students selected through multi-stage sampling technique. Two instruments titled Test Anxiety Inventory (TAI) and Examination Malpractice Attitude Scale(EMAS) were used for data collection. Data collected from the study were analysed using descriptive statistics and Regression analysis. Results obtained from the study indicated thatmost of the students have high test anxiety. The result also showed that few of the students have positive attitude towards examination malpractice. Moreso, the result revealed that test anxiety is not a significant predictor of secondary school students’attitude towards examination malpractice. The researchers recommended that secondary school counsellors should identify and implement interesting programmes and strategies for reducing test anxiety among students as it will help them to build negative attitude towards examination malpractice. Also that parents and caregivers should encourage their children and wards to develop negative attitude towards examination malpractice by providing them with the necessary support and logistics such as learning materials in order to enable them prepare adequately for examinations, among others.